2018
DOI: 10.2196/jmir.8382
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social Network Sites for Communication Among Health Professionals: Systematic Review

Abstract: BackgroundAlthough much research has been done investigating the roles of social network sites (SNSs) in linking patients and health professionals, there is a lack of information about their uses, benefits, and limitations in connecting health professions only for professional communication.ObjectiveThis review aimed to examine the utilization of SNSs for communication among health professionals in (1) frontline clinical practice, (2) professional networks, and (3) education and training to identify areas for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(137 citation statements)
references
References 49 publications
10
108
1
3
Order By: Relevance
“…As the world has arguably become more connected than ever and information exchange is nearly effortless, there are new opportunities for social media to be used for professional purposes. A recent systematic review found 33 studies evaluating the impact of social networking on communication and information sharing among health care professionals of various types, including physicians, pharmacists, and nurses, among others . Most of these were cross‐sectional studies or interviews and found that social networking was used as a tool in frontline clinical practice, to build a professional network, and for teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the world has arguably become more connected than ever and information exchange is nearly effortless, there are new opportunities for social media to be used for professional purposes. A recent systematic review found 33 studies evaluating the impact of social networking on communication and information sharing among health care professionals of various types, including physicians, pharmacists, and nurses, among others . Most of these were cross‐sectional studies or interviews and found that social networking was used as a tool in frontline clinical practice, to build a professional network, and for teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review found 33 studies evaluating the impact of social networking on communication and information sharing among health care professionals of various types, including physicians, pharmacists, and nurses, among others. 4 Most of these were cross-sectional studies or interviews and found that social networking was used as a tool in frontline clinical practice, to build a professional network, and for teaching and learning. There is limited literature, however, on how pharmacists use social media.…”
Section: Introductionmentioning
confidence: 99%
“…This approach allowed us to reach a broader group of doctors, especially junior physicians and young specialists. Nowadays, when social media is more and more involved in medical networking, information dissemination and professional interaction [10], we considered it a good opportunity to involve colleagues this way.…”
Section: Particularities Of the Romanian Choosing Wisely In Internal mentioning
confidence: 99%
“…Nonetheless, these channels have not been fully utilized to promote dementia literacy. Social media has been shown to be an effective channel for health education and for communication among health professionals [24]. For example, developing an app for assessing dementia symptoms in older citizens is a project that is worthy of support.…”
Section: Conceptual Framework Of Dementia Literacymentioning
confidence: 99%